Production of Activated Carbon from Sewage Sludge for the Removal of Lead from Water - Rehman, Saeed Ur (2012)
Master of Science thesis in Chemical Engineering by Saeed ur Rehman entitled, "Production of Activated Carbon from Sewage Sludge for the Removal of Lead from Water," submitted in June 2012. Thesis advisor is Dr. Dana Abouelnasr and thesis co-advisor is Dr. Kevin Loughlin. Available are both soft and hard copies of the thesis.